Safety and efficacy of mechanical thrombectomy with Solitaire in patients with acute ischemic stroke - R.V. Narayana; Rajesh Pati; Sibasankar Dalai (Indian Journal of Neurosurgery, 2014)
Background Stroke is the third most common cause of death. Ischemic stroke accounts for 87% of all strokes. The standard treatment for acute ischemic stroke (AIS) is IV recombinant tissue plasminogen activator for patients who can reach the hospital with in 4.5 h. A rapid and complete recanalization is a major factor in good clinical outcomes in the treatment of acute cerebral ischemia. Stent-based recanalization techniques are increasingly used in stroke caused by large vessel occlusion, with promising results.